Analysis and evaluation costs of the operator products of aircraft during the warranty - Мачалін, І.О. (Proceedings of National Aviation University (archive), 2007)
An analysis and estimation of expenses of exploiter is made in the period of action of obligations of guarantees of supplier of wares of aviation technique. Analytical expressions, allowing to estimate these expenses taking into account the indexes of control authenticity, types of reserving of the systems and control periodicity, are developed.